ENCAPSULATION OF RED GINGER OLEORESIN (ZINGIBER OFFICINALE VAR RUBRUM) WITH CHITOSAN AS WALL MATERIAL - Jayanudin; Rochmadi (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: This research aims to determine the effect of the spray drying condition against encapsulation efficiency and characterization microcapsules of red ginger oleoresin. Methods: Preparation of encapsulation begun with the formation of emulsions by mixing red ginger oleoresin with chitosan solution which was dissolved with acetic acid 2% (v/v). The weight ratio of chitosan with red ginger oleoresin was 1: 1, 2: 1 and 3: 1 and then stirred using a homogenizer while added 2 ml tween 80 for 10 min. The size of emulsion droplet was measured using nanoparticle analyzer (NPA). The emulsion is formed and then inserted into the feed tank of a spray dryer. Inlet temperature of the spray dryer used in the 180 °C, 190 °C and 200 °C; and the spray dryer outlet temperature was 85 °C, feed rate at 2 L/h. The microcapsules formed were then analyzed encapsulation efficiency and characterization using scanning electron microscopy (SEM) and fourier transform infrared spectroscopy (FTIR). Results: Based on the research that has been done, the smallest effective diameter of the emulsion droplets was 216.4±1.5 nm and the largest was 2109.2±46.1 nm. The value of encapsulation efficiency ranged between 83.33±0.42%-99.15±0.02%. Increasing the weight ratio of chitosan with red ginger oleoresin and increase the spray drying inlet temperature, the encapsulation efficiency is also increased. The highest encapsulation efficiency was 99.15±0.02% occurred at 200 °C of spray drying inlet temperature and the weight ratio of chitosan with red ginger oleoresin of 3:1. Morphology analysis of the surface of microcapsules using scanning electron microscope (SEM) showed that the inlet temperature of 200 °C was obtained microcapsules with smooth surfaces. The Fourier transforms infrared spectroscopy (FTIR) analysis results indicating the absence of new compounds is formed. Conclusion: This research indicates that the spray drying conditions affecting the encapsulation efficiency and morphological characteristics of the red ginger oleoresin microcapsules.